Science and religion
1 online resource (ix, 346 pages)
Keywords: "This collection offers new perspectives on the study of science and religion, bringing together articles that highlight the differences between epistemological systems and call into question the dominant narrative of modern science. The volume provides historical context for the contemporary discourse around religion and science, detailing the emergence of modern science from earlier movements related to magic and other esoteric arts, the impact of the Reformation on science, and the dependence of Western science on the so-called Golden Age of Islam. In addition, contributors examine the impacts of Western science and colonialism on the ongoing theft of the biological resources of traditional and indigenous communities in the name of science and medicine. The volume's multi-perspectival approach aims to refocus the terms of the conversation around science and religion, taking into consideration multiple rationalities outside of the dominant discourse. "--